Penggunaan Aplikasi Software Geometer`S Sketchpad pada Pembelajaran Matematika untuk Peningkatan Pemahaman Konsep Transformasi Siswa - Asmawati Asmawati (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2019)
The research objective is to improve the ability to understand the concept of material transformation through the implementation of ICT-based learning using the Sketchpad Geometer software for Karai 1 Tebat Middle School students in Kepahiang District. Method, this research is a comparative descriptive study. The sample is grade IX students totaling 30 people. Data analysis uses descriptive comparative analysis. After descriptive comparative continued reflective. The results of the study, an increase from the initial conditions the average value of students from 44.67 to 65.83 in the first cycle and rose to 77.42 in the second cycle. So that from the initial conditions to the first cycle, increased by 44.37%, from the initial conditions to the second cycle increased by 73.33% and classified as high category. The results of observations of student activity increased in the learning process with a high category. Conclusion, the use of ICT-based media using the Sketchpad Geometer Software can improve students' conceptual understanding skills in the transformation of material, and can improve student activities. Keywords: Geometer`s Sketchpad Software, Concept Understanding